Acute myeloid leucaemia presenting as a rapidly progressive polyradiculoneuropathy. (18th November 2015) - Hirst, Claire L; Willis, Mark; Hussain, Hussain; Powell, Rob
Abstract : Neurological involvement at onset in acute myeloid leucaemia (AML) is rare, with only a few isolated case reports. We present the case of a 46-year-old man with rapidly progressive polyradiculoneuropathy as the presenting feature of AML. The proposed mechanism for this is postulated to be direct intraneural infiltration, although a paraneoplastic, autoimmune-related phenomenon could be possible. Despite chemotherapeutic intervention, the patient died 1 month after initial presentation. Although rare, neurological manifestations of AML do occur and it is important to include haematological malignancies in the differential diagnosis in patients presenting with neurological symptoms.